2011
DOI: 10.1007/s00345-011-0655-6
|View full text |Cite
|
Sign up to set email alerts
|

The muscarinic receptor antagonist propiverine exhibits α1-adrenoceptor antagonism in human prostate and porcine trigonum

Abstract: PurposeCombination therapy of male lower urinary tract symptoms with α1-adrenoceptor and muscarinic receptor antagonists attracts increasing interest. Propiverine is a muscarinic receptor antagonist possessing additional properties, i.e., block of L-type Ca2+ channels. Here, we have investigated whether propiverine and its metabolites can additionally antagonize α1-adrenoceptors.MethodsHuman prostate and porcine trigone muscle strips were used to explore inhibition of α1-adrenoceptor-mediated contractile respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 23 publications
(39 reference statements)
0
5
0
1
Order By: Relevance
“…Pharmacological treatment can be offered to those patients to reduce the voiding as well as the storage symptoms (25). Historically alpha 1 -blockers were mainly used to relieve the voiding symptoms, but the latest studies showed that non-selective antimuscarinics can reduce the storage symptoms acting through the M 3 receptor and voiding symptoms through the M 1–2 blockade (2628). …”
Section: Bladder Neck and Lutsmentioning
confidence: 99%
“…Pharmacological treatment can be offered to those patients to reduce the voiding as well as the storage symptoms (25). Historically alpha 1 -blockers were mainly used to relieve the voiding symptoms, but the latest studies showed that non-selective antimuscarinics can reduce the storage symptoms acting through the M 3 receptor and voiding symptoms through the M 1–2 blockade (2628). …”
Section: Bladder Neck and Lutsmentioning
confidence: 99%
“…İnsan ve domuzlarda yapılan başka bir çalışmada propiverin metabolitlerinin yine alfa 1 reseptörlerini bloke ettiği gösteril-miştir (19). Propiverinin NANK mekanizmaya ait ATP bağımlı mesane aşırı aktivitesini de baskılamakta olduğu, ayrıca detrusor kasılmasından sorumlu faktörlerden biri olan purinerjik mekanizmayı da kısmen inhibe ettiği öne sürülmektedir (20).…”
Section: Karma Etki Mekanizmasıunclassified
“…Such cross-reactivity can also be observed with targets less closely related to the primary binding partner of a ligand. For example, various histamine receptor antagonists bind to muscarinic receptors (54), and the muscarinic receptor antagonist propiverine binds with similar affinity to all subtypes of muscarinic receptors but also to all three subtypes of ␣ 1 -AR (206) and also inhibits L-type Ca 2ϩ channels (205). Interestingly, metabolites of propiverine exhibited a differential ratio of affinity for muscarinic receptors vs. ␣ 1 -AR and/or vs. L-type Ca 2ϩ channels ( Table 2).…”
Section: Selectivity Within and Outside Target Familymentioning
confidence: 99%
“…Selectivity problems with transporter inhibitors have long been known from the group of monoamine uptake inhibitors Data are based on radioligand binding studies at M3 muscarinic receptors and ␣1A-adrenoceptor (AR) with similar affinities at other subtypes of these receptors as reported by Wuest et al (205,206). Data on L-type Ca 2ϩ channels are based on electrophysiological recordings in human urinary bladder smooth muscle cells as reported by Wuest et al (204).…”
Section: C511mentioning
confidence: 99%